Socio onomastic approaches to the study of the urban linguistic landscape - Zlatina Nikolova (Progress in Science, 2024)
The article examines the urban landscape as a reflection of the complex interaction between language and society, emphasizing the importance of linguistic expressions in the urban environment. In the context of sociolinguistics, language is not only a means of communication, but also a sensitive indicator of social change. Through socio-onomastic and sociolinguistic approaches, it is possible to analyze urban spaces where linguistic signs such as road signs, billboards and place names play a central role in revealing cultural diversity and social dynamics.